Current Topics (The Muslim world, 1934)
The Secretary of the Nizam of Hyderabad on Missions Two Korans from Istanbul A New Chinese Translation of the Koran Dr. Ahmed Fahmy of Changchow “The Age of Ignorance” The Gospel of Barnabas once more! Relics of the ancient Faith Marriage and Divorce in Egypt Moslems Pray for President Roosevelt